Analisis Pesan-Pesan Dakwah Pada Thoha TV - Muhammad Irfansyah; Abdur Razzaq; Hidayat HT (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
This thesis is entitled "Analysis of Da'wah Messages on Thoha TV". The purpose of this study is as follows, namely to find out how the preaching messages carried out by Thoha TV Dakwah Media in conveying their da'wah messages and then to find out the supporting and inhibiting factors of Thoha TV's preaching when conveying their da'wah messages. This type of research is a qualitative research. There are two sources of data used and contained in this thesis, namely primary data and secondary data. Data collection techniques use interview techniques, documentation techniques, observation techniques, and sampling techniques. Based on the research results that have been obtained, the Da'wah messages contained on Thoha TV are da'wah messages that discuss issues of Aqidah (belief), issues of Morals, Syari'ah issues and issues of Muhamalah. Supporting factors found on Thoha TV are da'wah media that are adequate and supportive in spreading da'wah through the media, preachers who have character and are competent in conveying their da'wah. Besides that, Thoha TV also found inhibiting factors, namely internal and external problems.